2019
DOI: 10.12998/wjcc.v7.i20.3377
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase-negative anaplastic large cell lymphoma masquerading as Behcet's disease: A case report and review of literature

Abstract: BACKGROUNDAnaplastic large cell lymphoma (ALCL) is a CD30-positive T cell lymphoma, a rare type of non-Hodgkin lymphoma. The current World Health Organization classification system divides ALCLs into anaplastic lymphoma kinase (ALK)-positive and ALK-negative groups. ALCL rarely presents in the gastrointestinal tract.CASE SUMMARYA 54-year-old male was admitted to the department of gastroenterology for abdominal pain. He presented with lower abdominal pain, diarrhea and recurrent oral and penile ulcers. He was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Cutaneous manifestations of ALCL have been noted in the literature to mimic dermatologic conditions such as eczema, pyoderma gangrenosum, and squamous cell carcinoma [ 17 ]. Luo et al [ 2 ] reported a case of ALK-negative ALCL presenting as Behcet's disease, with recurrent penile and oral ulcers initially treated with steroids without improvement and later diagnosed 4 weeks later with penile tissue biopsy. Oliveira et al [ 3 ] described a case of pcALCL presenting as a large pyogenic granuloma mimicking skin infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous manifestations of ALCL have been noted in the literature to mimic dermatologic conditions such as eczema, pyoderma gangrenosum, and squamous cell carcinoma [ 17 ]. Luo et al [ 2 ] reported a case of ALK-negative ALCL presenting as Behcet's disease, with recurrent penile and oral ulcers initially treated with steroids without improvement and later diagnosed 4 weeks later with penile tissue biopsy. Oliveira et al [ 3 ] described a case of pcALCL presenting as a large pyogenic granuloma mimicking skin infection.…”
Section: Discussionmentioning
confidence: 99%
“…ALCL is a malignancy of CD30-positive T lymphocytes with distinct immunophenotypic characteristics. The 2016 revision of the World Health Organization classification of lymphoid neoplasms classifies ALCL into four categories: primary cutaneous, systemic anaplastic lymphoma kinase (ALK) positive, systemic ALK-negative, and breast implant-associated ALCL [ 2 ]. Primary cutaneous ALCL (pcALCL) has an indolent course with a 5-year survival rate of up to 96% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anaplastic large cell lymphoma (ALCL) is a rare CD30-positive T-cell non-Hodgkin lymphoma. The 2017 World Health Organization classification, which is the most recent classification, categorizes ALCL into anaplastic lymphoma kinase (ALK)-positive ALCL and ALK-negative ALCL [ 1 ]. The extranodal involvement of ALCL is rarer in the gastrointestinal tract than in the bones and bone marrow [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%